Elevating Performance: Spiritual Leadership and Mitigation of Counterproductive Work Behavior in Higher Education - Subhaktiyasa, Putu Gede; Sintari, Silvia Ni Nyoman (Universitas Pendidikan Ganesha, 2024)
The role of spiritual leadership in reducing deviant behavior contrary to higher education objectives is limited. This study aimed to examine the effect of spiritual leadership on counterproductive work behavior through the mechanism of spiritual well-being. The study was quantitative research of an exploratory predictive nature involving 310 lecturers of private higher education institutions determined through random sampling techniques. Data were obtained through a closed questionnaire distributed online and analyzed through PLS-SEM with a reflective model using SmartPLS. Findings demonstrated that spiritual leadership has a significant negative effect on counterproductive work behavior and a significant positive impact on spiritual well-being. In addition, spiritual well-being significantly negatively affected counterproductive work behavior. The study provides an understanding of the influential role of spiritual well-being in mediating the effect of spiritual leadership on counterproductive work behavior. The findings indicate that implementing spiritual leadership tends to improve spiritual well-being and reduce the deviant behavior of lecturers. The study contributes a comprehensive understanding of integrating spiritual aspects into higher education management to promote harmonious academic ethics and environment.